Aplikasi Kompos Tandan Kosong Kelapa Sawit Untuk Pertumbuhan Bibit Kakao (Theobroma cacao L.) Pada Ultisol di Polibag - Alfan Zarano Akbar; Yulistiati Nengsih; Rudi Hartawan (Jurnal Media Pertanian, 2023)
Oil palm empty fruit bunches are a source of organic matter rich in nutrients N, P, K, and Mg. TKKS has the properties of helping nutrient solubility, improving soil structure, water absorption capacity, and carbon source, and providing energy for soil microorganisms needed for plant growth. This study aimed to determine the effect of composting empty palm oil bunches on the growth of cocoa seedlings. The materials used are F1 cocoa seeds (high-quality seeds) aged three months, polybags measuring 15 x 30 cm, TKKS fertilizer, NPK 15-15-15 fertilizer, and ultisol. The equipment used is a set of tools for seeding cocoa, scales, tape measure, paranet, calipers, and an electric oven. The research design was a one-factor complete randomized design. TKKS fertilizer treatment design (k) with four dose levels in 3 kg of planting medium, namely: k0 = control, k1 = 100 g, k2 = 200 g, k3 = 300 g. Parameters observed were plant height, stem diameter, shoot dry weight, root dry weight, media moisture content, soil physical and chemical analysis. The data obtained were analyzed statistically using analysis of variance. If the variance analysis results have a significant effect, continue using the DNMRT test at the level of α = 5%. TKKS fertilizer treatment at a dose of 300 g produced cocoa seedlings aged six months with a height of 54.33 cm, stem diameter of 10.02 mm, dry crown weight of 33.13 g, root dry weight of 15.56 g, and media moisture content without watering for five day of 6.71%. TKKS compost is an effective soil fertilizer to support the growth of cocoa seedlings.